Access to crop digital information and the sharing of benefits derived from its use: Background and perspectives. Issue 3 (27th April 2020) - von Wettberg, Eric; Khoury, Colin K.
Abstract : Crop diversity remains as valuable to global food security as ever. Yet information about this diversity seems to have become nearly as important as the seeds themselves. With the advent of high‐throughput DNA sequencing technologies and emerging "phenomic" approaches, and new platforms to store and explore the data they generate, the ways in which our global community can produce and access this information, and share the benefits of its use, is rapidly changing, creating a set of challenges that we will explore in a special collection of papers in Plants, People, Planet .